Zero to Three Dimension Structure Evolution from Carbon Allotropes to Phosphorus Allotropes. Issue 5 (23rd December 2022) - Ye, Xiaohui; Qi, Ming; Chen, Mengzhen; Zhang, Lihui; Zhang, Jinying
Abstract: As the promising and highly‐focused materials after silicon, carbon, and phosphorus promote the development of nanotechnology due to its allotropes with unique structures and properties. The carbon allotropes of 0D fullerene, 1D carbon nanotube, and 2D graphene stimulate the investigation of structures, synthesis, properties, and further applications of carbon nanomaterials. Analogous to carbon, phosphorus is demonstrated to have a rich phase diagram. 0D phosphorus fullerenes, 1D phosphorus nanotubes and fibrous red phosphorus, and recently 2D black phosphorene and violet phosphorene have unique structures analogous to carbon fullerene, carbon nanotube, and graphene, is developed. The photoelectronic properties and further applications of the phosphorus allotropes as semiconductors, energy storage materials, biomaterials, and sensors are also investigated. Great efforts are dedicated to studies of the synthesis, structure, and properties of carbons and phosphorus. However, there is no systematic review of the structure of phosphorus allotropes compared to carbon allotropes. Herein, the structures along with possible future perspective of carbon and phosphorus allotropes review and compare in this work based on the classification of different dimensions. Abstract : Great efforts are dedicated to studies the synthesis, structure, and properties of carbons and phosphorus. However, as the promising and highly‐focused materials after silicon, the development of carbon and phosphorus allotropes is still undiscussed. Herein, a systematic review, comparison and the possible future perspective of carbon and phosphorus allotropes, is provided based on the classification of different dimensions.